2022
DOI: 10.3389/fonc.2022.828259
|View full text |Cite
|
Sign up to set email alerts
|

Value of Whole-Thyroid CT-Based Radiomics in Predicting Benign and Malignant Thyroid Nodules

Abstract: The objective of this research is to explore the value of whole-thyroid CT-based radiomics in predicting benign (noncancerous) and malignant thyroid nodules. The imaging and clinical data of 161 patients with thyroid nodules that were confirmed by pathology were retrospectively analyzed. The entire thyroid regions of interest (ROIs) were manually sketched for all 161 cases. After extracting CT radiomic features, the patients were divided into a training group (128 cases) and a test group (33 cases) according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The findings of the study demonstrate that a machine learning model using quantitative radiomics features can accurately predict the malignancy of TNs. In contrast to previous studies, 9,[27][28][29] we incorporated multimodel fusion during model construction and implemented model interpretation methods to enhance decision transparency. The fusion model's radiomics signature displayed a higher predictive value compared with using only a single LASSO regression model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the study demonstrate that a machine learning model using quantitative radiomics features can accurately predict the malignancy of TNs. In contrast to previous studies, 9,[27][28][29] we incorporated multimodel fusion during model construction and implemented model interpretation methods to enhance decision transparency. The fusion model's radiomics signature displayed a higher predictive value compared with using only a single LASSO regression model.…”
Section: Discussionmentioning
confidence: 99%
“…However, many thyroid diseases have multiple nodules, irregular shapes, and ambiguous boundaries, making it difficult to accurately describe thyroid lesions. In addition, individual nodules cannot reflect the full picture of thyroid lesions 9 …”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, DECT has improved the noninvasive evaluation of thyroid nodules, and an increasing number of studies have indicated that quantitative parameters derived from DECT, especially quantitative IC, can distinguish benign from malignant thyroid nodules (6,9,(14)(15)(16). However, there are few relevant studies exploring the applications of DECT, and some of them show contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultrasound-based radiomics has been applied to the prediction of cervical lymph node metastasis [7][8][9] as well as BRAF-V600E mutation in thyroid cancer. 10,11 Meanwhile, this technique has been widely used in discriminating the nature of thyroid nodules [12][13][14][15] and achieved good results. However, its fusion models with artificial intelligence (AI) are diverse, and its diagnostic performance is also uneven.…”
Section: Introductionmentioning
confidence: 99%